ANESTEZJOLOGIA I INTENSYWNA TERAPIAPerioperative glucose control in patients undergoing major thoracic surgical procedures – the role of anaesthesia and analgesia - Werner, Małgorzata; Misiołek, Hanna; Strojek, Krzysztof; Knapik, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : The presence of hyperglycaemia during surgery and the perioperative period is associated with poor clinical outcomes, particularly in diabetic patients undergoing major surgical procedures. While the perioperative stress response may be managed by intensive insulin therapy, the choice of anaesthetic technique and pain control can also alleviate the metabolic response via its impact on the sympathetic system. Aim : The aim of the study was to assess the impact of two types of anaesthesia and perioperative analgesia on glycaemic control in type 2 diabetic and non diabetic patients undergoing major thoracic operations. Material and methods: 80 patients, aged 57 ±9 years undergoing elective thoracic surgical procedures were enrolled in the study. Patients were divided into 4 groups: I – general and thoracic epidural anaesthesia (TEA), non-diabetic patients; II – total intravenous anaesthesia (TIVA), non-diabetic patients; III – general and TEA, patients with type 2 diabetes mellitus; IV – TIVA, patients with type 2 diabetes mellitus. Postoperative analgesia was provided by patient-controlled TEA with ropivacaine (groups I and III) or patient-controlled analgesia (PCA) with morphine (groups II and IV). An intensive insulin therapy protocol was implemented in all patients, aiming for a target glucose range of 80-110 mg/dl. Glycaemic values and insulin requirements during anaesthesia and three postoperative days were evaluated. Results: No significant differences between the groups were found with respect to mean ±SD blood glucose levels or insulin requirements during anaesthesia. Postoperative glucose levels and insulin requirements were not different in studied patients and did not depend on analgesia type either. Conclusion : The type of anaesthesia and postoperative analgesia has no influence on glycaemia and insulin requirements in type 2 diabetic and non diabetic patients undergoing major thoracic surgery.